An AN ANALYSIS OF SURABAYA RIVER CARRING CAPACITY BASED ON THE LAND-USE DIFFERENCES - Yulfiah Yulfiah Yulfiah (Lowland Technology International, 2019)
Surabaya River has been indicated receiving a great pressure from the activities of people living and industries along the river. Currently, this river is still the major source of water supply for Water Source Department in Surabaya City (“PDAM Surabaya”). For this reason, the prediction of carring capacity in Surabaya River is needed. The ecosystem degradation is expected to decrease. The calculation is based on the differences of the existing land-use in the Surabaya watershed. The results of the load capacity demonstrate that the maximum BOD (Biologycal Oxygen Demand) and permitted BOD waste have a relatively wide tolerance span on some segments. Therefore, it takes a long time to reach critical points and positions on some segments. However, the maximum tolerance of BOD load and BOD of waste permitted in the dry season is lower than in the rainy season. Briefly, excessive waste disposal must be controlled to create a sustainable ecosystem in Surabaya River.